2022
DOI: 10.1136/bmjopen-2021-054206
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pre-anaesthetic assessment clinic: a systematic review of randomised and non-randomised prospective controlled studies

Abstract: ObjectivesThe aim of this systematic review was to examine the effectiveness of pre-anaesthesia assessment clinics (PACs) in improving the quality and safety of perioperative patient care.DesignSystematic review.Data sourcesThe electronic databases CINAHL Plus with Full Text (EBSCOhost), Medline and Embase (OvidSP) were systematically searched on 11 September 2018 and updated on 3 February 2020 and 4 February 2021.Eligibility criteriaThe inclusion criteria for this study were studies published in English or Sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…59 Perioperative optimization performed by anesthesiologists through the perioperative surgical home has helped decrease patient length of stay, improve quality, and lower the cost of care. 60 It allows an efficient approach to screen patients for surgery that better identifies and optimizes medically complex patients. 61 While clinical care pathways improve certain measurable disparities, they do not address individual patient and clinician factors that can drive disparities.…”
Section: Clinical Care Pathwaysmentioning
confidence: 99%
“…59 Perioperative optimization performed by anesthesiologists through the perioperative surgical home has helped decrease patient length of stay, improve quality, and lower the cost of care. 60 It allows an efficient approach to screen patients for surgery that better identifies and optimizes medically complex patients. 61 While clinical care pathways improve certain measurable disparities, they do not address individual patient and clinician factors that can drive disparities.…”
Section: Clinical Care Pathwaysmentioning
confidence: 99%
“…It is effective tool to obtain the patients current and past medical history, vital statistics to identify the multifactorial perioperative risks which requires plan of management before anesthesia and surgery [1]. Preanesthetic assessment reduces the cancellation of surgery, length of stay hence reduces the cost and enhances patient safety [2]. Inadequate preoperative evaluation and poor patient preparation significantly increases the odds of complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It has been shown that pre-anaesthetic assessment may reduce patient anxiety regarding perioperative care, rate of surgery, cancellation or postponement, and length of hospital stay. 5 Moreover, the omission of pre-anaesthetic assessment is associated with, for example, a higher risk of unanticipated adverse perioperative events and a negative impact on patient outcomes. 5 Despite being very common and essential for many patients undergoing surgery, the literature provides no standard definition of pre-anaesthesia assessment.…”
Section: Introduction 1| Rationalementioning
confidence: 99%
“…5 Moreover, the omission of pre-anaesthetic assessment is associated with, for example, a higher risk of unanticipated adverse perioperative events and a negative impact on patient outcomes. 5 Despite being very common and essential for many patients undergoing surgery, the literature provides no standard definition of pre-anaesthesia assessment. 3 Consequently, little is known about the different pre-anaesthetic assessment approaches (who, where, and why the particular choice of approach) and which outcomes, including patient satisfaction and patient perceptions of the quality of health services, are assessed.…”
Section: Introduction 1| Rationalementioning
confidence: 99%